(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
The article deals with pedagogical conditions of educating future teachers in a humane spirit using ethnopedagogical materials. The importance of ethnopedagogy in the educational process is emphasized and the main methods of its application in teacher training are highlighted. Practical recommendations on integration of ethnopedagogical materials into educational programs are offered.